Targeting the sAC-Dependent cAMP Pool to Prevent SARS-Cov-2 Infection - Aslam, Muhammad (Cells, 2020)
An outbreak of the novel coronavirus (CoV) SARS-CoV-2, the causative agent of COVID-19 respiratory disease, infected millions of people since the end of 2019, led to high-level morbidity and mortality and caused worldwide social and economic disruption. There are currently no antiviral drugs available with proven efficacy or vaccines for its prevention. An understanding of the underlying cellular mechanisms involved in virus replication is essential for repurposing the existing drugs and/or the discovery of new ones. Endocytosis is the important mechanism of entry of CoVs into host cells. Endosomal maturation followed by the fusion with lysosomes are crucial events in endocytosis. Late endosomes and lysosomes are characterized by their acidic pH, which is generated by a proton transporter V-ATPase and required for virus entry via endocytic pathway. The cytoplasmic cAMP pool produced by soluble adenylyl cyclase (sAC) promotes V-ATPase recruitment to endosomes/lysosomes and thus their acidification. In this review, we discuss targeting the sAC-specific cAMP pool as a potential strategy to impair the endocytic entry of the SARS-CoV-2 into the host cell. Furthermore, we consider the potential impact of sAC inhibition on CoV-induced disease via modulation of autophagy and apoptosis.